Comparative Study of PVDF Sheets and Their Sensitivity to Mechanical Vibrations: The Role of Dimensions, Molecular Weight, Stretching and Poling - Mrlík, Miroslav; Osička, Josef; Cvek, Martin; Ilčíková, Markéta; Srnec, Peter; Gorgol, Danila; Tofel, Pavel (Nanomaterials (Basel, Switzerland), 2021)
This paper is focused on the comparative study of the vibration sensing capabilities of poly(vinylidene fluoride) (PVDF) sheets. The main parameters such as molecular weight, initial sample thickness, stretching and poling were systematically applied, and their impact on sensing behavior was examined. The mechanical properties of prepared sheets were investigated via tensile testing on the samples with various initial thicknesses. The transformation of the α-phase to the electro-active β-phase was analyzed using FTIR after applying stretching and poling procedures as crucial post-processing techniques. As a complementary method, the XRD was applied, and it confirmed the crystallinity data resulting from the FTIR analysis. The highest degree of phase transformation was found in the PVDF sheet with a moderate molecular weight (Mw of 275 kDa) after being subjected to the highest axial elongation (500%); in this case, the β-phase content reached approximately 90%. Finally, the vibration sensing capability was systematically determined, and all the mentioned processing/molecular parameters were taken into consideration. The whole range of the elongations (from 50 to 500%) applied on the PVDF sheets with an Mw of 180 and 275 kDa and an initial thickness of 0.5 mm appeared to be sufficient for vibration sensing purposes, showing a d33 piezoelectric charge coefficient from 7 pC N-1 to 9.9 pC N-1. In terms of the d33, the PVDF sheets were suitable regardless of their Mw only after applying the elongation of 500%. Among all the investigated samples, those with an initial thickness of 1.0 mm did not seem to be suitable for vibration sensing purposes.
Keywords: vibration sensing; d33; physical properties; crystallinity; poly(vinylidene fluoride)